Bahasa Inggris - Rola Manjaleni; Cut Intan Amalia; Dian Anita (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2026)
Village fund management is a critical mechanism in Indonesia's decentralized governance framework, especially following the enactment of Law No. 6 of 2014 on Villages, which mandated substantial annual budget transfers directly to village governments. This study analyzes the financial management practices of Cipedes Village, Paseh Sub-district, Bandung Regency, through the lens of four core financial governance principles: transparency, accountability, participatory governance, and budget discipline. Using a qualitative descriptive approach based on in-depth interviews with village officials and document analysis, the study finds that Cipedes Village has implemented a systematic financial management system supported by the Siskeudes (Village Financial System) application, public information dissemination through deliberative forums and physical banners, and multi-tiered supervisory mechanisms. However, challenges persist—including low digital literacy among residents, delayed fund disbursement, dependence on BUMDes (Village-Owned Enterprise) revenue as bridge funding, and insufficient contingency planning for unforeseeable events. The study concludes with policy recommendations to improve village financial governance through digital education, inclusive forum scheduling, and greater alignment between village-level realities and higher-level government policies.